Pengaruh Mekanisme Corporate Governance Terhadap Praktik Earnings Management Pada Badan Usaha Sektor Perbankan Indonesia (Studi Empiris Pada Perbankan yang Listing Di Bursa Efek Indonesia) - Widodo, Satria Teguh; , Dr. Fatchan Achyani, SE, M.Si (2016)
The study aims to examine the effect of corporate governance mechanisms, namely the board size, the composition of the independent board, managerial ownership, institutional ownership and existence of the audit committee on the practice of earnings management that occurred in the banking company listing on the Indonesia Stock Exchange. The population of this research is all Indonesian banking companies listed in Indonesia Stock Exchange from 2008 until 2013. The company analyzed were 90 (15x6) banking companies listed in Indonesia Stock Exchange from 2008 up to 2013. The sample selection based on a purposive sampling. The study's hypotheses were tested using multiple linear regression. The results show that institutional ownership and existence of audit committee significant effect on earnings management by the respective probability of 0,010 and 0,001. As for the board size, the composition of the independent board, and managerial ownership has no significant effect with a probability value of 0.363, 0.636 and 0.440 in which the value of p> 0.05. Similarly, the test results showed that Fhitung-F larger than F table (4.178> 2.37) and the value of p <0.05. This means that the hypothesis is supported, meaning together no influence between corporate governance mechanisms against earnings management practices.